Immune Response of Broiler Chickens Fed Diets Supplemented with Different Level of Chromium Methionine under Heat Stress Conditions - S. K. Ebrahimzadeh; P. Farhoomand; K. Noori (Asian-Australasian Journal of Animal Sciences, 2012)
The objectives of this study were to investigate the immune responses of broiler chickens fed diets supplemented with different level of chromium methionine (CrMet) in heat stress (HS) condition. Two hundred and eighty eight male broiler chickens (Ross 308) were allocated to four treatment groups (supplementation with 0, 200, 400 or 800 ppb Cr in the form of CrMet) in a completely randomized design. The experiment was conducted at heat stressed condition and all birds were kept under temperature of 33±2°C. Antibody titers against Newcastle disease virus (NDV) and infectious bronchitis virus (IBV), heterophil to lymphocyte ratios (H/L), and concentration of plasma cortisol (CPC) were measured at 21 and 42 d. At 42 days of age two birds were chosen randomly from each replicate, slaughtered, spleen and bursa of Fabricius were collected, weighed and expressed as a percentage of live body weight. Antibody titers against NDV and IBV at 21 and 42 days of age in broiler fed supplemental CrMet were higher than in broiler chickens fed control diet (p<0.05). CPC level in broiler chickens fed CrMet were significantly (p<0.05) decreased. Increases in lymphocyte counts and consequently a decrease in heterophil to lymphocyte ratios in broiler chickens fed 800 ppb Cr were observed at 21 and 42 d. Supplementation with CrMet had no significant effect on lymphoid organs of broilers. The results suggest that dietary CrMet supplementation at a level of 800 ppb can improve some immune responses of broiler chickens under heat stress conditions.